2020
DOI: 10.3389/fchem.2020.00242
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sodium Alginate on the Flotation Separation of Molybdenite From Chalcopyrite Using Kerosene as Collector

Abstract: In this paper, the effect of sodium alginate (SA) on the flotation separation of molybdenite (MoS 2) from chalcopyrite using kerosene as collector was systematically investigated. The results of single-mineral micro-flotation tests indicated that SA exhibited strong depression on chalcopyrite flotation while it imposed no impact on the floatability of molybdenite. However, in the chalcopyrite-molybdenite mixed-mineral flotation system, the presence of chalcopyrite significantly increased the depressing effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Then, the filter cake was dried in a vacuum oven at 25 °C. After completely evaporating the moisture, 1 mg of dry solid was mixed with 100 mg of spectroscopy-grade KBr for analysis …”
Section: Methodsmentioning
confidence: 99%
“…Then, the filter cake was dried in a vacuum oven at 25 °C. After completely evaporating the moisture, 1 mg of dry solid was mixed with 100 mg of spectroscopy-grade KBr for analysis …”
Section: Methodsmentioning
confidence: 99%
“…Research has shown that sodium alginate is effective in the flotation separation of scheelite from calcite and fluorite using sodium oleate as a collector. Sodium alginate has the potential to chelate calcium minerals and then hydrophilic their surface in solution [63,64].…”
Section: Industrial Applicationsmentioning
confidence: 99%
“…Calcium carbonate is thought to promote the recovery of chalcopyrite for the following reasons: (1) The addition of calcium carbonate changes the pH and Eh of the pulp, affecting the flotation recovery of chalcopyrite [23][24][25]; (2) The residual starch on the surface of the chalcopyrite reacts with the added calcium ions and adsorbs on the surface of the chalcopyrite, which impacts the inhibition of chalcopyrite by DCMT. Studies have shown that metal ions in the solution can be adsorbed on the mineral surface through ion exchange or chelation and affect the interaction between the flotation agents and minerals, particularly silicates [26][27][28][29].…”
Section: Flotation Testsmentioning
confidence: 99%